2005
DOI: 10.1152/japplphysiol.00013.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sarcoplasmic reticulum Ca2+-ATPase overexpression in postinfarction rat myocytes

Abstract: balance.In most animal models of heart failure as well as human heart failure, SR Ca 2ϩ uptake activities and SERCA2 expression were depressed (13, 15). Focusing on the rat model of myocardial infarction (MI), Afzal and Dhalla (1) first showed depressed ATP-dependent Ca 2ϩ uptake in SR membrane fractions isolated from rat left ventricles (LV) at 4, 8, and 16 wk after MI. Specifically, maximal velocity of ATP-dependent Ca 2ϩ uptake by SR membranes was decreased, but affinity for Ca 2ϩ was unchanged. Follow-up s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
8
0
1
Order By: Relevance
“…By contrast, the persistent decrease in left ventricular −dP/dt and elevated LVEDP in AMD3100-treated post-MI rats suggests that cellular events implicated in relaxation remain dysfunctional. Calcium uptake by SERCA2 plays an integral role in ventricular relaxation and decreased protein expression, and activity was reported in cardiac myocytes isolated from 3-week post-MI rats [1,21,31]. Although protein content and activity were not measured in the present study, the persistent downregulation of SERCA2 mRNA in AMD3100-treated post-MI rats indirectly provides a plausible mechanism contributing to impaired relaxation.…”
Section: Discussionmentioning
confidence: 53%
“…By contrast, the persistent decrease in left ventricular −dP/dt and elevated LVEDP in AMD3100-treated post-MI rats suggests that cellular events implicated in relaxation remain dysfunctional. Calcium uptake by SERCA2 plays an integral role in ventricular relaxation and decreased protein expression, and activity was reported in cardiac myocytes isolated from 3-week post-MI rats [1,21,31]. Although protein content and activity were not measured in the present study, the persistent downregulation of SERCA2 mRNA in AMD3100-treated post-MI rats indirectly provides a plausible mechanism contributing to impaired relaxation.…”
Section: Discussionmentioning
confidence: 53%
“…Normal intracellular Ca 2+ handling in cardiomyocytes is maintained by multiple proteins, including L-type Ca 2+ channels, NCX, RyR2 and Ca 2+ -ATPase. 22,23 In the present study, we investigated whether choline affected calcium stores and found that the inhibitory effect of choline on [Ca 2+ ] i overload is not mediated by RyRs. Fig.…”
Section: Discussionmentioning
confidence: 88%
“…In myocardial infarction and human heart failure, there is a decrease in the expression of serca2a which is hallmark of cardiac myocyte dysfunction [4043]. Studies depict that decrease in the expression of serca2a leads to decrease in contractility in rats after MI and increase in the expression of serca2a can lead to augmented contractility in cardiovascular diseases [44,45]. Ryanodine receptor in the sarcoplasmic reticulum works in conjunction with the serca2a and helps maintaining calcium levels by calcium efflux [46].…”
Section: Discussionmentioning
confidence: 99%